Creating Plant Anatomy Structure Model using Science, Technology, Religion, Engineering, Arts, Mathematics (STREAM) Approach - Tri Wahyu Agustina; Mar’atus Sholikha; Asrianty Mas’ud; Lia Amelia (Perhimpunan Intelektual Muslim Indonesia, 2022)
The purpose of this study was to analyze the achievement of science-technology-religion-engineering-arts-mathematics (STREAM) aspects on products made by students. The product in question is in the form of a report of a Plant Anatomy structure model project. This research uses The Static-Group Comparison Design. Purposive sampling was carried out on 39 Biology Education students of class A in semester IV with project assignments without intervention through the STREAM approach (regular class). The intervention class, 38 students of class C in semester IV with project assignments using the STREAM approach (intervention class). Each student designs and creates one of the structure models of either roots, stems, or leaves. Students also make the project report, where the project report assignment guideline is in the form of a performance task. The research instrument of this study is an analytical rubric along with a score of 0 - 4 with certain criteria and field notes. The data measured in this study is the percentage of achievement on certain criteria. The results showed that the engineering aspect was the strongest in the intervention class, reaching the